Design and Development of ARM based Electronic Test Evaluation System for RTO - Shweta Salokhe; U. L. Bombale (International Journal of Reconfigurable and Embedded Systems (IJRES), 2016)
Electronic  test  evaluation  system  for  driving  license  is  very  useful  now  a  days,  as  there  is   increase  in  the  human  intervention  in  the  system.  This  system  make  the  driving  license  procedure  transparent  to  human  being. The  proposed  technological  solution  is advancement  towards    the  automation  of  system  and  improves  the  driving  test accuracy. As  a  contribution  to  society  this system  reduces  the  number  of  road  accidents occurs due to untrained drivers.